2016
DOI: 10.1123/jpah.2016-0066
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Street Intervention for Walking to Transit, Nontransit Walking, and Bicycling: A Quasi-Experimental Demonstration of Increased Use

Abstract: Background Complete streets require evaluation to determine if they encourage active transportation. Methods Data were collected before and after a street intervention provided new light rail, bike lanes, and better sidewalks in Salt Lake City, Utah. Residents living near (<800 m) and far (≥801–2000 m) from the street were compared, with sensitivity tests for alternative definitions of near (<600 and <1000 m). Dependent variables were accelerometer/global positioning system (GPS) measures of transit trips, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 43 publications
2
36
0
4
Order By: Relevance
“…However, a distance effect was observed in the larger sample of residents in this same neighborhood. Residents living near the complete street after it was completed increased their active travel along the complete street corridor and used it more than residents living farther away (Brown et al, 2016). Other studies have found a distance effect after a two year follow-up after the intervention was completed (Goodman et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, a distance effect was observed in the larger sample of residents in this same neighborhood. Residents living near the complete street after it was completed increased their active travel along the complete street corridor and used it more than residents living farther away (Brown et al, 2016). Other studies have found a distance effect after a two year follow-up after the intervention was completed (Goodman et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, following a California complete street renovation there was no increase in cyclists, but a 37% increase in pedestrians (Shu et al, 2014); these mixed findings are difficult to interpret because no comparison street was included to control for potential shifting of transportation practices over time. Although street renovations are sometimes related to more self-reported walking (Pazin et al, 2016) or accelerometer-measured walking (Brown et al, 2016), other studies show no increased use after street renovations (Boarnet et al, 2013) or greenway construction (West and Shores, 2011, 2015). Past evaluations of the complete street reported in the current study showed more nearby residents used complete street transit than before (Brown et al, 2015), and more people were counted at transit stops than before (Werner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Исследование Moving Across Places (MAPS) [26,27] обобщило результаты практической реализации в США подхода улучшения инфраструктуры, подразумевающего модернизацию не всего района проживания, а так называемой "полной улицы" (Complete Street). Политика "полных улиц" приобрела популярность в 2000-х годах и принята к реализации в 30 из 50 штатов США [28].…”
Section: изменения инфраструктуры в проспективных исследованияхunclassified
“…По результатам исследования для расстояния проживания от "полной улицы" выявлен самостоятельный эффект на ФА. Так, время транспортной и рекреационной ФА выше у участников исследования, близко проживающих (800 метров) к "полной улице", по сравнению с далеко и очень близко живущими (1000 и 600 метров) [27]. Аналогичные тенденции (статистически не значимые) выявлены по времени пользования велосипедами.…”
Section: изменения инфраструктуры в проспективных исследованияхunclassified